Doses of renin-angiotensin system inhibitors but not beta-blockers predict outcome after ST-elevation myocardial infarction. Issue 5 (3rd September 2019) - Liu, Pei-Yu; Chen, Chien-Lin; Yu, Min-Chien; Ko, Yu-Lin; Hsu, Shun-Yi; Chou, Hsin-Hua; Yeh, Kuan-Hung; Duan, De‑Min; Chen, Ming-Hsin; Lin, Jeng-Feng
ABSTRACT: Objectives : In patients with ST-elevation myocardial infarction (STEMI), it is not clear whether low-dose renin-angiotensin system inhibitors and beta-blockers can result in the same benefits achievable with higher target doses. This observational study aims to investigate whether higher doses of angiotensin converting enzyme inhibitors (ACEI)/angiotensin II receptor blockers (ARB) and beta-blockers can improve outcomes in patients with STEMI. Methods : We recorded daily doses of ACEI, ARB, and beta-blockers in 331 patients with STEMI. Echocardiographic studies were performed at baseline and were repeated 6 months later. Clinical events, including all-cause death and heart failure, were followed for 2 years. Results : Patients receiving high-dose ACEI/ARB had less increase in left ventricular end-diastolic volume index (LVEDVI) at 6 months. In multivariable linear regression model, ACEI/ARB dose or beta-blocker dose was not an independent predictor of increase in LVEDVI at 6 months. Kaplan-Meier survival curves showed that doses of ACEI/ARB ( p = 0.003) and beta-blockers ( p = 0.027) were significant predictors of death and heart failure. In multivariable Cox regression analysis, independent predictors of all-cause death and heart failure were diabetes mellitus ( p = 0.001), left ventricular ejection fraction ( p = 0.026), and ACEI/ARB dose ( p = 0.025). Beta-blockers dose was not a predictor of clinical events in multivariable analysis ( p = 0.413). Conclusion : High-dose ACEI/ARB, but not beta-blocker, was associated with lower rate of all-cause death and heart failure in patients with STEMI.